2000
DOI: 10.1096/fj.00-0584fje
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary calcium on adipocyte lipid metabolism and body weight regulation in energy‐restricted aP2‐agouti transgenic mice

Abstract: We have demonstrated previously a regulatory role for intracellular Ca2+ ([Ca2+]i) in adipocyte lipogenesis and lipolysis and have recently reported that 1,25-(OH)2-D increases adipocyte [Ca2+]i, which causes increased lipogenesis and decreased lipolysis. We have now tested the hypothesis that suppressing 1,25-(OH)2-D by increasing dietary calcium will suppress adipocyte [Ca2+]i, thereby facilitating weight loss by stimulating lipolysis and inhibiting lipogenesis in calorically (Kcal)-restricted (70% of ad lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
197
2
14

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(221 citation statements)
references
References 40 publications
(61 reference statements)
8
197
2
14
Order By: Relevance
“…Weight loss in subjects consuming an energyrestricted diet that had a moderate level of protein and lowcalcium content (16% energy from protein, 600 mg Ca/d) was equal to subjects consuming an equicaloric diet that was higher in both protein and calcium (27% energy from protein, 1600 mg Ca/d). 11 Weight reduction in obese women was the same in calcium-supplemented (1800 mg Ca/d) and placebo groups (800 mg Ca/d). 12 Our findings contrast a weight loss study (energy deficit of À2 MJ/d for 24 wk) in obese adults where weight loss of subjects allocated to a high dairy diet (1200-1300 mg Ca/d, n ¼ 11) was À10.9% compared to À8.6% in a supplemental calcium group (1200-1300 mg Ca/d, n ¼ 11) and À6.5% in a low-calcium group (500 mg Ca/d, n ¼ 10).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Weight loss in subjects consuming an energyrestricted diet that had a moderate level of protein and lowcalcium content (16% energy from protein, 600 mg Ca/d) was equal to subjects consuming an equicaloric diet that was higher in both protein and calcium (27% energy from protein, 1600 mg Ca/d). 11 Weight reduction in obese women was the same in calcium-supplemented (1800 mg Ca/d) and placebo groups (800 mg Ca/d). 12 Our findings contrast a weight loss study (energy deficit of À2 MJ/d for 24 wk) in obese adults where weight loss of subjects allocated to a high dairy diet (1200-1300 mg Ca/d, n ¼ 11) was À10.9% compared to À8.6% in a supplemental calcium group (1200-1300 mg Ca/d, n ¼ 11) and À6.5% in a low-calcium group (500 mg Ca/d, n ¼ 10).…”
Section: Discussionmentioning
confidence: 90%
“…Two standard servings of alcohol (10 g alcohol/serving) were permitted per wk. EB was achieved by increasing energy intake by 2 MJ/d for each 0.5 kg weight loss per wk (averaged over wk [8][9][10][11][12]. 17 Subjects were provided with a prescriptive meal plan.…”
Section: Dietary Interventionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] We have shown that 1a, 25-dihydroxyvitamin D mediates increases in intracellular calcium ([Ca 2 þ ]i) in adipocytes via the 1a, 25-dihydroxyvitamin D-membraneassociated rapid response steroid hormone (1, 25D 3 -MARRS) binding protein, stimulates lipogenesis and inhibit lipolysis via a calcium-dependent mechanism. 4,5 We have also shown a dose-responsive inhibition of uncoupling protein 2 expression by 1a, 25-dihydroxyvitamin D in adipocytes; this is a genomic effect, presumably mediated by the nuclear vitamin D receptor (nVDR).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, based on results showing that women consuming less than 600 mg calcium/d had an increased percentage body fat (4) , the existence of a threshold of usual calcium intake below which a supplementation in this mineral would effectively promote fat mass loss is possible. The first objective of the present study was to investigate this hypothesis and to assess the impact of a calcium plus vitamin D (calciumþD) supplementation on the outcome of a weightreducing programme in female low-and very low-calcium consumer (VL-CC) overweight/obese subjects.Up to now, the potential effect of calcium on energy balance and adiposity has been explained by a suppression of calcitriol (1,25-dihydroxyvitamin D) which decreases intra-adipocyte calcium influx and concentration (5) leading to a reduced lipogenic gene expression and stimulation of lipolysis and adipocytes uncoupling protein 2 expression (6,7) .Moreover, a diet high in calcium was also shown to increase 24 h lipid oxidation (8) and to reduce lipid absorption due to the intestinal formation of calcium-fatty acids insoluble 'soaps' that are excreted in the faeces (9) . From another perspective, the idea of a 'calcium-specific appetite control' was proposed by Tordoff (10) who documented the possibility that low calcium intake or stores might trigger episodes of increased desire to eat and stimulate motivation to seek out or choose calcium-containing items, and potentially other nutrients and/or food 'recognised' as calcium-rich (10) .…”
mentioning
confidence: 99%